38 CHA2DS2-VASc score and B-type natriuretic peptide in predicting stroke, transient ischemic attack, thromboembolism and death in at-risk patients without atrial fibrillation – the STOP-HF experience. (16th October 2019) - Kerr, B; Rebabonye, P; McDonald, K; Ledwidge, M; O' Connell, E; Watson, C; Gallagher, J
Abstract : Background: In recent years, use of the CHA2DS2-VASc score in predicting stroke/TIA has extended beyond AF. It is recognized that the cluster of multiple stroke risk factors included within the CHA2DS2-VASc score increases the risk of stroke/TIA whether or not AF has been defined. Similarly, natriuretic peptides have gained interest as a marker of cardiovascular risk. Increased blood levels of natriuretic peptides have been repeatedly associated with cardioembolic stroke. Purpose: To determine the accuracy of the CHA2DS2-VASc score and BNP separately for predicting stroke or transient ischaemic attack (TIA) and the composite endpoint of Stroke/TIA/Thromboembolism (TE) and Death in patients without a history of atrial fibrillation or flutter, and to evaluate the incremental benefit of adding BNP to CHA2DS2-VASc for predicting stroke or TIA, in a community-based population. Methods: The study included 801 patients without known AF enrolled in the STOP HF follow-up study between 2012 and 2017. The end points measured were stroke/TIA and the composite end point of ischaemic stroke/TIA/TE and death. Results: The study population (N=801) had a mean age (SD) of 64.4 years (10.4) with 381 (47.6%) male. The median B-type Natriuretic peptide was 24pg/ml (Interquartile range:12- 52). A total of 33 (4.1%) patients had a CHA2DS2-VASc of 1, while 175 (21.9%), 282 (35.2%), 186 (23.2%), 94 (11.7%), 31 (3.9%) had CHA2DS2-VASc score of 1, 2, 3, 4 and >/=5 respectively. The composite endpoint of stroke/TIA/TE/Death occurred in 115 (14.4%) of the population. The incidence of stroke/TIA/TE and death occurred more frequently as the CHA2DS2-VASc score increased. The outcome occurred in 1 (3%), 15(8.6%), 33 (11.7%) and 35 (18.8%) 19 (20.2%), 12 (38.7%) of those with a CHA2DS2-VASc score of 0, 1, 2, 3, 4 and ≥5 respectively. Separately, at baseline, both the CHADS2-Vasc score and the BNP predicted Stroke/TIA. The adjusted odds ratio for Stroke/TIA using the CHADS2-Vasc score and the baseline BNP were 2.05 (95% CI, 1.43 -2.93) and 1.33 (95% CI, 0.88- 2.0) respectively. Both the CHA2DS2-VASc score and the BNP had a respectable discrimination performance in this group with a c statistic of 0.72 for the former and 0.67 for the latter. Adding the BNP to the CHADS2Vasc score improved the stroke/TIA predictive value further, producing a c statistic of 0.75. The adjusted odds ratios for Stroke/TIA, TE and Death using the CHA2DS2-VASc score and the baseline BNP were 1.35 (95% CI, 1.12 -1.63) and 1.5 (95% CI, 1.21- 1.87) respectively (both p<0.01). Addition of BNP to the CHA2DS2-VASc improved c- statistics from 0.64 to 0.68 for stroke/TIA/TE and death. Conclusion: Both the CHA2DS2-VASc tool and BNP predict Stroke and TIA and the composite end-point of stroke/TIA/TE and death in patients with out atrial fibrillation at baseline. The predictive value of CHA2DS2-VASc is further enhanced with the addition of BNP for outcome measures.